The Influence Factor for the Successful Implementation of Cleaner Production: A Review - Yusup, Mohd Zaki; Wan Mahmood, Wan Hasrulnizzam; Salleh, Mohd Rizal; Mohd Razali, Muhamad (Universiti Teknologi Malaysia, 2014)
Cleaner Production (CP) is an environmental management strategy that is being implemented based on social-technical approach. It has been proved to be adapted at every stage of the manufacturing process particularly in establishing the green factory. Even so, the implementation performance of this practice is still depends on several critical factors to be successful. The review has disclosed that social responsiveness; legislation compliance’s and economic performance are the element that has a high influence level for the successful implementation of this practice. The ability to underline these elements has been seen able to assist manufacturers to identify the strength and weaknesses of the implementation process. This eventually motivates the manufacturer to develop a significant guideline in establishing the sustainable environmental practices and consequently increases the manufacturing performance and strengthens the ability to continuously compete in global markets.